(untitled) (Tribhuvan University Journal, 2017)
Art therapy is used for healing or treatment of some health problems. For such healing, arts like painting, sculpture, music, drama, dance and poetry are used. Art is related to creativity whereas therapy is related to cure, treatment and healing. Art therapy includes creation, appreciation and healing. Art therapy may help individuals manage and cope with mental health problems, physical pain, difficult emotions, feelings and experiences. It allows people to be free from anxiety and use their imagination for something positive. Art therapy is highly useful to solve mental health problem and disorder in behavior. Whenever other methods of treatment become ineffective, art therapy can be a main form of treatment. However, the power of art for treatment has been ignored in our context. If the domain of art is linked to medical treatment, the cure of the disease can be easier. This attempt may add new dimensions in the field of treatment and healing. This article attempts to elaborate the concept of art therapy, how it can be applied in healing and various types of art therapies.